2009
DOI: 10.1264/jsme2.me08547
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-Rich Microhabitats within Biofilms Are Synchronized with the External Environment

Abstract: The nutrient ion concentrations in the interstitial waters of biofilms (BFs) formed on reed and stone surfaces were investigated in the northern and southern basins of Lake Biwa over several years. The following were observed for both types of BF: 1) Concentrations of ammonium, nitrate, nitrite, and phosphate ions were much (hundreds to thousands of times) higher in the BFs than in the surrounding lake water; 2) the concentration of ions, especially nitrate ions, in the BFs changed seasonally, being higher fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…The dramatic in crease in EEA may also be linked to differential rates of enzyme expression related to changes in bacterial community composition (Martinez et al 1996). Thus, although the present study lacked the resolution to differentiate between several possible underlying mechanisms, heterotrophic biofilm development is highly responsive to the availability of resources, effectively storing (Tsuchiya et al 2009) and cycling available resources. Ultimate limits are probably imposed by physicochemical constraints such as shear strength and diffusion gradients (Battin et al 2003, Besemer et al 2007) -conditions likely to be found in biofilms in later successional stages rather than in the communities, described in the present study, that developed in 3 wk.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The dramatic in crease in EEA may also be linked to differential rates of enzyme expression related to changes in bacterial community composition (Martinez et al 1996). Thus, although the present study lacked the resolution to differentiate between several possible underlying mechanisms, heterotrophic biofilm development is highly responsive to the availability of resources, effectively storing (Tsuchiya et al 2009) and cycling available resources. Ultimate limits are probably imposed by physicochemical constraints such as shear strength and diffusion gradients (Battin et al 2003, Besemer et al 2007) -conditions likely to be found in biofilms in later successional stages rather than in the communities, described in the present study, that developed in 3 wk.…”
Section: Discussionmentioning
confidence: 92%
“…These results suggest that turnover in biofilms is a result of internal cycling supported by biofilm structural and community responses to enrichment. Structurally, increased biofilm thickness protects extracellular enzymes from being washed out of the system by downstream flow, and it allows biofilms to concentrate nutrients (Tsuchiya et al 2009) and energy-yielding materials (Battin et al 1999) -which are dispersed in planktonic communities. This protection probably also encourages the production of extracellular enzymes by quorum sensing (DeAngelis et al 2008, Decho et al 2010, diffusion sensing (Redfield 2002), or efficiency sensing (Hense et al 2007), which occur when concentrations of small, energy-inexpensive signal molecules reach threshold levels, inducing the transcription of large, energy-expensive extracellular enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm is generally defined as an aggregate of microbes that formed on the surfaces [1][2][3][4]. These microbial aggregates have been found almost in all aquatic ecosystems from fresh water until ocean.…”
Section: Introductionmentioning
confidence: 99%
“…The matrix of biofilms was indicated as a highly hydrated matrix (interstitial water content up to 98%) [9,10]. The previous study showed that the concentrations of nutrient ions in the interstitial water of biofilms are hundreds to thousands of times greater than surrounding water [2,4]. These particular nutrient-rich environments inside the biofilm matrices are established from a very early stage of biofilm formation [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation